2011
DOI: 10.1016/j.tranpol.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Are intrazonal trips ignorable?

Abstract: Intrazonal trips are not always included in model estimation because they do not appear on a network in centroid-to-centroid travel. It is also presumed that their exclusion does not affect model results. This paper tests the above presumption by examining the assumptions of ignorable missingness. The results indicate that omitting intrazonal trips in model estimation result in biased sample. Consequently parameter estimates get biased. The paper also compares the results of travel mode choice models by exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…In a similar vein, Sadek et al [24] found that smart growth-related land use variables (e.g., land use diversity) affects intrazonal travel by encouraging walking or discouraging automobile travel. A more recent study by Bhatta and Larsen [23] also highlighted that "because (intrazonal trips) are shorter trips generally, it is widely believed that intrazonal trips are mostly nonmotorized trips such as walking and cycling" (p. 13). Then, they confirmed this belief through logistic regression analysis on mode choice.…”
Section: Structural Equation Modelingmentioning
confidence: 99%
“…In a similar vein, Sadek et al [24] found that smart growth-related land use variables (e.g., land use diversity) affects intrazonal travel by encouraging walking or discouraging automobile travel. A more recent study by Bhatta and Larsen [23] also highlighted that "because (intrazonal trips) are shorter trips generally, it is widely believed that intrazonal trips are mostly nonmotorized trips such as walking and cycling" (p. 13). Then, they confirmed this belief through logistic regression analysis on mode choice.…”
Section: Structural Equation Modelingmentioning
confidence: 99%
“…In practice, transportation modelers mainly focus on centroid-to-centroid flows and tend to exclude intra-zonal trips [30,35]. However, this leads to a biased sample and impedes proper model calibration [36,37]. In our case, this is especially true, since, despite the high resolution at the postal zone level, many shopping trips are very short, and a large proportion of all shopping trips are expected to be intra-zonal (i.e., a large share of groceries is expected to be sold to consumers inside the retailer zone).…”
Section: Intra-zonal Distance Estimationmentioning
confidence: 99%
“…Figure 5a shows the daily average inter-district trip distances measured based on approach 1 and approach 2, respectively. The daily average inter-district trip distance measured based on approach 1 assumes trips between two zones have the same origin and destination points (the centroid), which is unrealistic because the origin and destination of trips are usually scattered within a zone and influenced by time of day, trip purpose, and other district attributes (Bharat and Larsen, 2011). The daily average inter-district trip distance measured based on approach 2 is relatively shorter.…”
Section: Trip Distancementioning
confidence: 99%